Working Alliance and Functional Outcomes in an Occupational Therapy Intervention: A Cross Case Analysis - Morrison, Tricia L. (Université d'Ottawa / University of Ottawa, 2012)
This is the first known occupational therapy (OT) study to examine the emergent patterns of the client-therapist working alliance during the course of a community-based OT intervention. The experiences of both the adult client and OT in each of four dyads are explored and described as they relate to the evolution of the alliance over time and the impacting contextual factors. These experiences were considered alongside the therapy outcomes. Mixed methods, including quantitative scales and interviews, were used in this multiple-case study situated within a pragmatism paradigm. Individual case and cross case analyses were conducted leading to the identification of eleven cross case themes. These findings suggest that the interpersonal relationship between a client and OT develops with the goal of becoming a safe harbour for the clients. The strengthening interpersonal bond appears to create an impetus within the client to engage in therapeutic activities. This enticed engagement results in the client’s performance of novel activity purposefully selected by the OT as bearing personal meaning for the client. The clients’ engagement often results in enhanced insight into their abilities and meaningful functional gains. This success appears to reinforce and energize both the momentum toward the collaboratively-established therapy goals, as well as provides a positive feedback mechanism into the working alliance. The OT’s training, philosophy and skill, client’s attributes, and environmental influences (both physical and social) all appear to have potential implications upon the working alliance’s development and/or the therapeutic achievements. Further research will be needed to confirm or disconfirm these findings and may include further study with variable client populations (e.g., different ages, different conditions), the role of humour in the therapeutic process, the impact of client’s degree of social isolation on the alliance, as well therapists’ disparate levels of use-of-self and the related impacts upon the alliance.
Keywords: Occupational Therapy; Therapeutic Relationship; Working Alliance